Metergoline and cyproheptadine suppress prolactin release by a non-5-hydroxytryptaminergic, non-dopaminergic mechanism. - Besser, G; Delitala, G; Grossman, A; Yeo, T (1980)
A dispersed rat anterior pituitary cell system has been used to investigate the effects of cyproheptadine and metergoline on prolactin secretion. Both drugs were potent inhibitors of prolactin secretion. However, the inhibition was not antagonized by either 5-hydroxytryptamine or a variety of dopamine antagonists. We conclude that both drugs act through mechanisms that are neither 5-hydroxytryptaminergic nor dopaminergic.